Energy-efficient and reliable routing protocol for dynamic-property-based clustering mobile ad hoc networks. (January 2017) - Oh, Young-jun; Lee, Kang-whan
Mobile ad hoc networks comprise mobile nodes. The nodes both send and receive messages and can communicate with each other. Thus, the network builds its own network structure that is not dependent on the infrastructure. Owing to the characteristics of mobile ad hoc networks, they have been used in environments of poor communication, such as those in which the infrastructure cannot be built; for example, disaster areas and war zones. In this article, we propose an advanced energy-conserving optimal path schedule algorithm. The proposed algorithm sets the routing path using the relative angle, which is the distance between the source node and the base station. Using simulation results, we compared the proposed algorithm to existing algorithms. The protocol used by the proposed algorithm provides a higher packet delivery ratio and lower energy consumption than the lowest ID clustering algorithm and the mobility-based metric for clustering in the mobile ad hoc network algorithm.